2021
DOI: 10.1016/j.jaci.2021.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Developing a standardized approach for assessing mast cells and eosinophils on tissue biopsies: A Work Group Report of the AAAAI Allergic Skin Diseases Committee

Abstract: AAAAI Position Statements,Work Group Reports, and Systematic Reviews are not to be considered to reflect current AAAAI standards or policy after five years from the date of publication. The statement below is not to be construed as dictating an exclusive course of action nor is it intended to replace the medical judgment of healthcare professionals. The unique circumstances of individual patients and environments are to be taken into account in any diagnosis and treatment plan. The statement reflects clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 152 publications
(240 reference statements)
0
6
0
Order By: Relevance
“…Until such data are forthcoming, there remains no good evidence to justify pathologists to performing mast cell counts in the work-up of patients with suspected MCAS, a view also reflected in a recent set of clinical guidelines. 25 Functional Disorders (Chronic Diarrhoea Without an Identifiable Cause, 'Mastocytic Enterocolitis,' Irritable Bowel Syndrome, and Others)…”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Until such data are forthcoming, there remains no good evidence to justify pathologists to performing mast cell counts in the work-up of patients with suspected MCAS, a view also reflected in a recent set of clinical guidelines. 25 Functional Disorders (Chronic Diarrhoea Without an Identifiable Cause, 'Mastocytic Enterocolitis,' Irritable Bowel Syndrome, and Others)…”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
“…Larger controlled studies are required to determine with more certainty whether or not a clinically useful cutoff for mast cell density exists that would support a diagnosis of MCAS. Until such data are forthcoming, there remains no good evidence to justify pathologists to performing mast cell counts in the work‐up of patients with suspected MCAS, a view also reflected in a recent set of clinical guidelines 25 …”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
“…It is also worth noting that accumulations of tissue MCs can also be detected in various inflammatory disorders or genetic conditions. [43][44][45][46][47][48]…”
Section: Laboratory Valuesmentioning
confidence: 99%
“…However, an MC count of > 75-100/mm 2 is suggested to be abnormal, dependent on the location of the biopsy. [12][13][14] Recently, an MC percentage of > 40% was also demonstrated to be specific for CM, next in specificity to the distribution of MC in skin. 15 Expression of aberrant MC markers might also be related to certain subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed a wide range of MC density in lesional skin. However, an MC count of > 75–100/mm 2 is suggested to be abnormal, dependent on the location of the biopsy 12–14 . Recently, an MC percentage of > 40% was also demonstrated to be specific for CM, next in specificity to the distribution of MC in skin 15 .…”
Section: Introductionmentioning
confidence: 99%